Social Support and Sex Role Orientation as Predictors of Quality of Life in Senior Citizens (Global Journal of Human-Social Science, 2020)
The present study was aimed to explore the relationship of social support and sex role orientation with quality of life in senior citizens. The sample comprised of 400 senior citizens with equal number of educated males and females (200 each). The analysis revealed that for the male's sample, social support explained the maximum variance (5%) followed by femininity (4%) in quality of life. In all, these variables have accounted for 9% of the variance. In female's sample, only social support has contributed (5%) of variance. Further, t-test has revealed the superiority of males in masculinity, femininity and quality of life and female's superiority on social support.
Keywords: social support; sex-role orientation; quality of life; gender